Differences of Magnesium Level Between Normal Pregnancy and Preeclamsia - Pradipta, Rengga; Sriyanti, Roza; Bachtiar, Hafni (Andalas Obstetrics And Gynecology Journal, 2021)
Background: Preeclampsia is a multi-organ disorder that occurs in pregnant women with high blood pressure which is still difficult to predict. Until now, many theories have put forward the causes of preeclampsia, one of which is much debated is the lack of nutrition in pregnant women which can lead to preeclampsia. Several studies suggest that there is a relationship with the lack of micronutrient intake, especially magnesium, which causes preeclampsia, especially in developing countries. Magnesium deficiency is one possible factor causing severe preeclampsia. Magnesium plays a role in normal neuromuscular function, regulation of calcium, potassium and transport of sodium in the membrane as a regulation of the activation of ATP. Magnesium also plays a role in blood pressure regulation. Magnesium deficiency can lead to endothelial malfunction, hypertension and failure of the cardiovascular system. The role of magnesium is in enzyme reactions that bind to anaerobic glucose metabolism, the krebs cycle, fatty acid oxidation and reactions between coenzyme and fatty acids. Magnesium deficiency will result in changes to the nerves, muscles and blood vessels.Methods: Analytical observational study with cross sectional design in 17 women with preeclampsia and 17 normal pregnant women who met the inclusion and exclusion criteria. Research subjects were collected at Dr M Djamil Padang General Hospital, November 2019 to January 2020. Magnesium levels were checked by enzymatic methods. The difference in the mean magnesium preeclampsia and normal pregnancy was analyzed using independent t test.Results: Mean magnesium in preeclampsia was lower than normal pregnancy (1.61 ± 0.59aµg / ml vs 2.20 ± 0.18, p = 0.001).Conclusion: Mean magnesium level in preeclampsia was significantly lower than normal pregnancy..Keywords: Average levels of magnesium, magnesium, preeclampsia, normal pregnancy